2008
DOI: 10.1111/j.1365-2893.2008.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of universal hepatitis A immunization of children in Minsk City, Belarus: four‐year follow‐up

Abstract: Hepatitis A is a reportable disease in Belarus. Universal hepatitis A vaccination of children aged 6 years in Minsk City began in 2003. This analysis was conducted to evaluate the short-term impact of the program. Hepatitis A incidence data from 1954 to 2006 was compiled. Vaccination effectiveness was estimated by comparing the incidence of reported hepatitis A cases after 4 years of immunization (2006) with the incidence when the vaccination program started (2003). The vaccines used were Avaxim 160 or Avaxim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Data from CIIMS showed that the reported coverage of HepA was consistently greater than 90% among the target children during 2008-2016 in Shandong Province. Several countries or regions where routine vaccination is recommended have demonstrated the effectiveness of immunization on the incidence of hepatitis A (Zhu et al, 2013;Fisenka et al, 2008;Chironna et al, 2012;Zhang et al, 2014). The results of the present study also demonstrated that the reported incidence of hepatitis A had declined by up to 47% for those 1-15 years of age in 2014 when compared to 2006-2008 in Shandong Province, according to the data from the Chinese National Notifiable Disease Reporting System (NNDRS).…”
Section: Discussionmentioning
confidence: 99%
“…Data from CIIMS showed that the reported coverage of HepA was consistently greater than 90% among the target children during 2008-2016 in Shandong Province. Several countries or regions where routine vaccination is recommended have demonstrated the effectiveness of immunization on the incidence of hepatitis A (Zhu et al, 2013;Fisenka et al, 2008;Chironna et al, 2012;Zhang et al, 2014). The results of the present study also demonstrated that the reported incidence of hepatitis A had declined by up to 47% for those 1-15 years of age in 2014 when compared to 2006-2008 in Shandong Province, according to the data from the Chinese National Notifiable Disease Reporting System (NNDRS).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some areas implemented vaccination only in a particular region of a country (e.g. Puglia, Italy 38 ; or Catalonia, Spain where a combined hepatitis A and B vaccine was used 39 ) or only in one city (e.g., Minsk, Belarus 37 ), and were not included.…”
Section: Discussionmentioning
confidence: 99%
“…For review objectives 1 and 2, only observational studies conducted in a setting with UMV with monovalent, inactivated hepatitis A vaccines were included (Table S1). Studies from settings where hepatitis A vaccination was only implemented at the regional level (for example in Puglia, Italy 38 or Minsk City, Belarus 37 ), or from settings in which live attenuated hepatitis A vaccines or only combined hepatitis A vaccines were used in the UMV programs were excluded. Furthermore, studies in at risk populations, outbreak studies, modeling studies and economic evaluations were excluded; as were studies that did not present incidence or prevalence baseline data (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando o aumento de adultos jovens suscetíveis à infecção e a gravidade da doença para essa faixa etária, faz-se necessário o conhecimento dos profissionais de Saúde sobre a prevalência da hepatite viral A para identificar, avaliar e controlar as epidemias e calcular o impacto dos programas de vacinação 24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54 .…”
Section: -Introduçãounclassified